Contamination of Dental Unit Water and Air Outlets Following Use of Clean Head System and Conventional Handpieces - Mehrnoosh Sadighi; Sahand Rikhtegaran; Lida Toomarian; Siavash Savadi Oskoee; Parnian Alizadeh Oskoee (Tabriz University of Medical Sciences, 2007)
Background and aims. Dental handpiece is a source of contamination because it is in constant touch with the oral cavity. Sterilization does not seem to be sufficient to prevent penetration of microorganisms into air and water lines of the unit, because negative pressure developed by valves (which are placed in water outlets) and post shut-off inertial rotation of handpiece result in water and debris being sucked into air and water outlets of dental unit. The aim of this study was to compare dental unit contamination following use of clean head system handpieces and conventional handpieces. Materials and methods. Twenty-two dental units in the Department of Pediatric Dentistry in Shahid Beheshti Faculty of Dentistry were used for the purpose of this study. A 1.5×108 cfu/mm3 concentration of Staphylococcus epidermis (SE) was used to contaminate the air and water outlets of dental units. Ten clean head system handpieces and 10 conventional handpieces were used for 30 seconds in the above-mentioned suspension. Microbial samples were collected from the air and water lines. Culturing and colony counting procedures were carried out. Data was analyzed by t-test; a value of p< 0.01 was considered significant. Results. Results demonstrated a significantly lower SE contamination in water outlets following the use of clean head system (p< 0.01). Conclusion. A lower tendency of clean head system handpieces to transmit SE compared to conventional system makes them a better choice for infection control.